2011
DOI: 10.1158/0008-5472.can-11-0127
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Trastuzumab Resistance in Breast Cancer by Targeting Dysregulated Glucose Metabolism

Abstract: Trastuzumab shows remarkable efficacy in treatment of ErbB2-positive breast cancers when used alone or in combination with other chemotherapeutics. However, acquired resistance develops in most treated patients, necessitating alternate treatment strategies. Increased aerobic glycolysis is a hallmark of cancer and inhibition of glycolysis may offer a promising strategy to preferentially kill cancer cells. In this study, we investigated the antitumor effects of trastuzumab in combination with glycolysis inhibito… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
203
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(216 citation statements)
references
References 35 publications
12
203
0
1
Order By: Relevance
“…Moreover, oxamate also significantly enhanced the sensitivity of cancer cells to several chemotherapy agents (20)(21)(22). Here, in the present study, the effect of LDH-A inhibition by oxamate on NPC cells was explored, and the involved mechanisms were evaluated.…”
Section: Introductionmentioning
confidence: 92%
“…Moreover, oxamate also significantly enhanced the sensitivity of cancer cells to several chemotherapy agents (20)(21)(22). Here, in the present study, the effect of LDH-A inhibition by oxamate on NPC cells was explored, and the involved mechanisms were evaluated.…”
Section: Introductionmentioning
confidence: 92%
“…Indeed, many patients fail to benefit from these combined therapeutic approaches and there remains an urgent need for more efficient therapeutic strategies. It has been shown that targeting bioenergetic alterations sensitizes breast cancer cells to chemotherapy (9)(10)(11) and to biologic therapy, such as Herceptin (12). However, it is unclear whether cancer cell metabolic reprogramming may contribute to AI resistance and whether targeting it may sensitize cancer cells to AIs.…”
Section: Introductionmentioning
confidence: 99%
“…2-DG, a glucose analog, binds with HK competitively and inhibits glycolysis. Although as a single agent the antitumor effect was not significant, a study showed that 2-DG combined with trastuzumab inhibited trastuzumab-sensitive and resistant breast cancers in in vitro and in vivo models of HER-2 positive breast cancers with more efficient inhibition of glycolysis via downregulation of heat shock factor 1 and LDHA [69] . LDHA is the enzyme that catalyzes the conversion of pyruvate to lactate.…”
Section: Targeting Glycolytic Enzymesmentioning
confidence: 99%
“…Dichloroacetate (DCA), an inhibitor of pyruvate dehydrogenase kinase (PDK), may activate pyruvate dehydrogenase, which is governed by PDK, and facilitate the conversion of pyruvate to acetyl Co-A, which demonstrates the antiproliferative properties in highly metastatic diseases of DCA [71] . The inhibitor of LDH-A selectively inhibits the growth of HER-2-overexpressing cells and enhances the sensitivity of trastuzumab-resistant breast cancers to trastuzumab treatment [69,23] . Furthermore, downregulation of LDH-1 by oxamate shows a synergistical inhibitory effect on taxol-resistant breast cancer cells by promoting apoptosis when combined with taxol [9] .…”
Section: Targeting Glycolytic Enzymesmentioning
confidence: 99%